(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
We investigated potential differences in status inconsistency and time to return to work (RTW) from sickness absence between foreign-born and native Swedes, whether inconsistency was associated with RTW, and if this association was stronger for foreign-borns than natives. Significantly fewer native than foreign-born Swedes reported negative status inconsistency, but RTW did not differ between the groups and inconsistency was not associated with RTW. A positive selection of individuals to the Swedish labour market might help explain the findings. This first study of status inconcistency and RTW requires follow-ups in different settings of labour markets and insurance regulations.